Regional Variation in Pregnancy Outcomes amongst Women in Inflammatory Bowel Disease: A Population-Based Cohort Study - Parul Tandon; Christina Diong; Rachel Y. Chong; Geoffrey C. Nguyen (Canadian Journal of Gastroenterology and Hepatology)
Background. Women with inflammatory bowel disease (IBD) are at risk of certain pregnancy outcomes such as preterm delivery, infants small for gestational age (SGA), and Cesarean delivery. Whether regional variation in these outcomes exists remains unknown. We aimed to assess the geographical variation in these pregnancy outcomes in women with IBD. Methods. All pregnancies in women with and without IBD (2002-2013) were identified using Ontario health administrative datasets. Geographical variation in preterm delivery, infants SGA, and Cesarean delivery was assessed using age-adjusted odds ratios (aOR) with 95% confidence intervals (CI) comparing women with and without IBD, stratified by Ontario’s 14 health-service regions, known as Local Health Integration Networks (LHINs). Results. 1621 women with IBD (2466 pregnancies) and 855,425 women without IBD (1,280,493 pregnancies) were included. Women with IBD were more likely to have preterm delivery (aOR 1.56, 95% CI, 1.35–1.79), infants SGA (aOR 1.52, 95% CI, 1.23–1.88), and Cesarean section (aOR 1.34, 95% CI, 1.22–1.49). Significant geographical variation in these outcomes was detected, with the highest rates observed in the most northern rural areas (aOR for preterm delivery 2.78 (95% CI, 1.03–7.46), aOR for SGA 5.66 (95% CI, 1.67–19.14), and aOR for Cesarean delivery 2.48 (95% CI, 1.11–5.55)). There were no differences in these outcomes in women with and without IBD in more central urban LHINs. Conclusion. Significant regional variation was detected in rates of adverse pregnancy outcomes and Cesarean delivery in women with IBD. Further study is required to determine specific reasons for this variation.